Recent Progress in Direct Conversion of Methane to Methanol Over Copper-Exchanged Zeolites - Park, Min Bum; Park, Eun Duck; Ahn, Wha-Seung (Frontiers in Chemistry, 2019)
The conversion of methane into an easily transportable liquid fuel or chemicals has become a highly sought-after goal spurred by the increasing availability of cheap and abundant natural gas. While utilization of methane for the production of syngas and its subsequent conversion via an indirect route is typical, it is cost-intensive, and alternative direct conversion routes have been investigated actively. One of the most promising directions among these is the low-temperature partial oxidation of methane to methanol over a metal-loaded zeolite, which mimics facile enzymatic chemistry of methane oxidation. Thus mono-, bi-, and trinuclear oxide compounds of iron and copper stabilized on ZSM-5 or mordenite, which are structurally analogous to those found in methane monooxygenases, have demonstrated promising catalytic performances. The two major problems of theses metal-loaded zeolites are low yield to methanol and batch-like non-catalytic reaction systems challenging to extend to an industrial scale. In this mini-review, attention was given to the direct methane oxidation to methanol over copper-loaded zeolite systems. A brief introduction on the catalytic methane direct oxidation routes and current status of the applied metal-containing zeolites including the ones with copper ions are given. Next, by analyzing the extensive experimental and theoretical data available, the consensus among the researchers to achieve the target of high methanol yield is discussed in terms of zeolite topology, active species, and reaction parameters. Finally, the recent efforts on continuous methanol production from the direct methane oxidation aiming for an industrial process are summarized.